ADVANCE: Towards near real-time monitoring of vaccination coverage, benefits and risks using European electronic health record databases. (22nd December 2020) - Bollaerts, Kaatje; de Smedt, Tom; McGee, Chris; Emborg, Hanne-Dorthe; Villa, Marco; Alexandridou, Maria; Duarte-Salles, Talita; Gini, Rosa; Bartolini, Claudia; de Lusignan, Simon; Tin Tin Htar, Myint; Titievsky, Lina; et al.
Abstract: Background: The Accelerated Development of VAccine beNefit-risk Collaboration in Europe (ADVANCE) is a public-private partnership aiming to develop and test a system for rapid benefit-risk (B/R) monitoring of vaccines using European electronic health record (eHR) databases. This proof-of-concept study aimed to test the feasibility of near real-time (NRT) monitoring of vaccination coverage, benefits and risks based on multiple European eHR databases, using acellular pertussis vaccination in children aged <6 years as test case. Methods: A qualitative feasibility assessment on NRT monitoring was carried out using a survey and face-to-face discussion with ADVANCE data partners. Subsequently, a dynamic cohort study was conducted containing two distinct observation periods: a first period to establish a baseline (Jan 2014 to Mar 2018) and a subsequent 3-month period to test the actual feasibility of weekly NRT monitoring, based on which data latencies were calculated. An interactive web-application was additionally developed to facilitate the visual monitoring of vaccination coverage, the vaccine preventable disease incidence rates (benefits) and the incidence rates of adverse events (risks). Results: Nine databases from four countries (Denmark, Italy, Spain and UK) participated in the qualitative feasibility assessment. Of them, five databases took part in the dynamic cohort study, with 5 databases providing baseline data and 3 databases participating to the NRT monitoring, providing data extractions on an almost weekly basis. The median data latency (time between event date and data release date) was between 1 and 2 weeks except for the benefit and risk events in one of the databases (latency 16 weeks). Conclusion: Three European eHR databases successfully demonstrated the feasibility of providing data for weekly NRT monitoring, with short data latencies of 1–2 weeks for most events.